Leukocyte function and health status of calves supplemented with vitamins A and E - S. D. Eicher-Pruiett; J. L. Morrill; Frank Blecha; C. G. Chitko-McKown (Kansas Agricultural Experiment Station Research Reports, 1991)
Forty-four Holstein calves were fed milk replacers with varied concentrations of vitamins A and E from 3 to 45 d of age to determine their effects on concentrations of plasma vitamin A (retinol and retinyl palmitate) and vitamin E (a- tocopherol), lymphocyte and neutrophil functions, and health of calves. Plasma a-tocopherol was unaffected by increased vitamin A supplementation. Fecal scores, and eye and nose membrane responses were improved with increased vitamin A and lower vitamin E concentration, whereas the same treatment tended to reduce neutrophil cytotoxic and bactericidal activity by 6 wk of age. Increased supplemental vitamin E tended to enhance neutrophil functions. However, age appeared to have an effect on response to both vitamins.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Calves; Leukocytes; Vitamins; Health